« Toil of the noble world » : Pasquale Stanislao Mancini, Augusto Pierantoni and the international legal discourse of 19th century Italy - Elisabetta Fiocchi Malaspina (Clio@Themis)
The aim of this article is to reconstruct, from a legal historical point of view, the complexity and the meaning of international law in the Italian peninsula during the 19th century. The paper will analyse different entanglements that constituted the core of nineteenth-century Italian international legal discourse. It is structured in four sections, dealing respectively with : 1) the principle of nationality elaborated by Pasquale Stanislao Mancini and its repercussion both on private and public international law ; 2) the return to the historical origins of Italian international law and the role played by comparative constitutional law ; 3) the implementation and translation of particular legal genres, such as the attempts to codify international law ; 4) colonial education, including legal education, through the creation of the Scuola diplomatico-coloniale (colonial and diplomatic school).